1977
DOI: 10.1289/ehp.7720149
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods for hazards and health.

Abstract: The objective of this article is to document the need for further development of statistical methodology, training of more statisticians and improved communication between statisticians and the many other disciplines engaged in environmental research. Discussion of adequacy of the current statistical methodology requires the use of examples, which will hopefully not be offensive to the authors. Reference is made to recent developments and areas of unsolved problems delineated in three broad areas: enumeration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In 1971, the EPA established a 24-h average NAAQS for TSP of 260 µg/m 3 and an annual average of 75 µg/m 3 (38). In 1987, the EPA replaced the TSP standards with requirements for PM 10 : a 24-h average of 150 µg/m 3 and an annual average of 50 µg/m 3 averaged over three years (39). This change reflected an evolving understanding of the dosimetry of particles in the respiratory tract and improving measurement capability.…”
Section: Particulate Mattermentioning
confidence: 99%
See 3 more Smart Citations
“…In 1971, the EPA established a 24-h average NAAQS for TSP of 260 µg/m 3 and an annual average of 75 µg/m 3 (38). In 1987, the EPA replaced the TSP standards with requirements for PM 10 : a 24-h average of 150 µg/m 3 and an annual average of 50 µg/m 3 averaged over three years (39). This change reflected an evolving understanding of the dosimetry of particles in the respiratory tract and improving measurement capability.…”
Section: Particulate Mattermentioning
confidence: 99%
“…A Washington D.C. Circuit Court found that PM 10 is not an appropriate indicator for coarse particles and that the regulation of both PM 10 and PM 2.5 constitutes double regulation because the matter in PM 2.5 would also be a part of PM 10. The EPA recently called for a riskanalysis plan for PM 10-2.5 (the "coarse fraction" between 2.5 µm and 10 µm) and PM 2.5 and may revise the NAAQS to include a standard for the coarse fraction rather than PM 10 .…”
Section: Particulate Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature and rain fall plays key role in its life cycle such as its breeding, biting frequency and extrinsic incubation period [22]. Spectral analysis methods such as cross correlations and Fourier analysis has been used to study analyze correlates of epidemiological and environmental variables, for example to understand aggravation of asthma symptoms and daily minimum temperature [5], air pollution and mortality [16], and large-scale climatic oscillations and cholera epidemic [30]. In this work, we analyzed the cross correlation of Dengue with rainfall and temperature, and found that there is a lag of 9 weeks (20 weeks) between the peak of rainfall (average temperature) and peak of the Dengue incidences.…”
mentioning
confidence: 99%